Do serological tests for COVID-19 really help? About two cases - Rodríguez-Chávez, Luis Ángel (2021)
The COVID-19 epidemic has hit our country hard. Currently, we see how serological tests have become popular and they have been used not only for screening in early care but also in the diagnosis of the disease. The main concern that we have is whether in fact these tests could be useful in detecting theinfected patient in their period of contagion, since this is of special interest for public health. In this regard, two cases, of the many ones that exist today, are presented and a discussion on the subject is made.